2018
DOI: 10.1038/s41563-018-0088-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrifying model catalysts for understanding electrocatalytic reactions in liquid electrolytes

Abstract: Electrocatalysis is at the heart of our future transition to a renewable energy system. Most energy storage and conversion technologies for renewables rely on electrocatalytic processes and, with increasing availability of cheap electrical energy from renewables, chemical production will witness electrification in the near future. However, our fundamental understanding of electrocatalysis lags behind the field of classical heterogeneous catalysis that has been the dominating chemical technology for a long time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
116
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(124 citation statements)
references
References 35 publications
7
116
1
Order By: Relevance
“…Therefore, it is very challenging to identify actual active sites and determine the actual rate‐determining step during the reaction process . It was reported that Co 3 O 4 can retain its spinel crystal phase during the OER process . Thus, it is an ideal model material for in‐depth research of the real limiting factor of the OER process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is very challenging to identify actual active sites and determine the actual rate‐determining step during the reaction process . It was reported that Co 3 O 4 can retain its spinel crystal phase during the OER process . Thus, it is an ideal model material for in‐depth research of the real limiting factor of the OER process.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] It was reported that Co 3 O 4 can retain its spinel crystal phase during the OER process. [16,22,23] Thus,i ti sa ni deal model material for in-depth research of the real limiting factor of the OER process. Although the catalytic property of Co 3 O 4 is not satisfactory, enhancing conductivity and increasing active sites have been reported to effectively upgrade its OER performance.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very challenging to identify actual active sites and determine the actual rate‐determining step during the reaction process . It was reported that Co 3 O 4 can retain its spinel crystal phase during the OER process . Thus, it is an ideal model material for in‐depth research of the real limiting factor of the OER process.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, numerous investigations have been devoted to enhancing the electrocatalytic activities of TMs/NC by tuning the structures and components, including increase the number of active sites and boost the intrinsic activity . On the one hand, more surface‐active sites were successfully exposed by coupling different carbonaceous supports (e.g., carbon nanotubes, graphene, and carbon sphere), increasing the loading and decreasing the size of TMs . However, the limited surface space largely restricts the increase of the number of active sites, which prompt us to develop the porous carbonaceous materials as supports to extend more available body space loading TMs active species.…”
Section: Introductionmentioning
confidence: 99%